Effect of folded and crumpled morphologies of graphene oxide platelets on the mechanical performances of polymer nanocomposites. (26th June 2015) - Shang, Jin; Chen, Yuli; Zhou, Yanguang; Liu, Luqi; Wang, Guorui; Li, Xianglong; Kuang, Jun; Liu, Qing; Dai, Zhaohe; Miao, Hong; Zhi, Linjie; Zhang, Zhong
Abstract: Graphene and its chemical derivate have been taken as promising candidates in composites due to their extraordinary mechanical and physical properties. Different from conventional plate fillers, the embedded graphene fillers exhibit various morphologies (e.g. folded, crumpled, and distorted sheets) inside matrix because of its atomic thickness. In this work, we systematically investigated the influence of graphene oxide (GO) morphologies on the tensile properties of poly(vinyl alcohol)-based nanocomposites at low loading contents. Confocal laser scanning microscopy, as a characterization method, was employed to observe the morphologies of the embedded GO platelets. Tensile mechanical tests and in situ micro-Raman spectroscopy tests indicated that GO sheets with larger aspect ratios exhibited efficient interfacial load transfer and improved mechanical properties at ultra-low filler contents. However, with further increased nanofiller contents, the folded and crumpled GO sheets severely degraded the mechanical reinforcement as induced by interfacial debonding. Molecular dynamic simulation indicated obvious stress concentrations on the wrinkle throughout entire graphene platelet areas. Long-term creep tests confirmed the stress concentration eventually induced the decrease in creep resistance for nanocomposite at a high applied stress levels. All these results aided in understanding the mechanical behaviors of two-dimensional nanofiller-based nanocomposites with huge aspect ratios. Graphical abstract: Highlights: We investigate the influence of GO filler aspect ratios on mechanical properties of nanocomposites. Embedded GO sheets with large lateral size easily form folded and crumpled microstructures inside matrix. MD simulation indicate stress concentrations on the wrinkle throughout entire graphene area. GO sheets with large aspect ratio degrade the mechanical performance of nanocomposites at a high stress level.